A colorimetric sensor of H2O2 based on Co3O4–montmorillonite nanocomposites with peroxidase activity. (4th January 2018) - Zhu, Xixi; Chen, Wei; Wu, Kaili; Li, Hongyu; Fu, Min; Liu, Qingyun; Zhang, Xiao
Abstract : Schematic of the colorimetric detection of H2 O2 catalyzed using Co3 O4 –MMT NPs. Abstract : Herein, Co3 O4 nanoparticles deposited on montmorillonite (Co3 O4 –MMT NPs) were synthesized via a facile method and characterized by energy-dispersive X-ray spectroscopy (EDS), powder X-ray diffraction (XRD), and transmission electron microscopy (TEM). Significantly, the as-prepared Co3 O4 –MMT NPs were demonstrated to possess an intrinsic peroxidase-like activity, which could rapidly catalytically oxidize the peroxidase substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB·2HCl) by H2 O2, accompanied by a visible color change (colorless to blue); these NPs were then used to develop a sensitive colorimetric sensor for the detection of H2 O2 . The catalytic reaction of Co3 O4 –MMT NPs followed the Michaelis–Menten kinetics equation, and the composites showed good affinity towards TMB. Via the proposed method, H2 O2 can be detected in the range of 10–100 μM with a low detection limit (DL) of 8.7 μM. Fluorescence data reveal that electron transfer among the catalyst, TMB, and H2 O2 may contribute to the peroxidase-like activity of the Co3 O4 –MMT NPs. Finally, a colorimetric method was proposed for the detection of H2 O2, and the robustness of the Co3 O4 –MMT NPs was quite good. The sensor of H2 O2 based on Co3 O4 –MMT NPs can exhibit great potential applications in the medical, food, and environmental fields.